SIZING UP CRYSTALS AND THEIR MELT INCLUSIONS: A NEW APPROACH TO CRYSTALLIZATION STUDIES - Roggensack K. (My University, 2001)
A correlation between melt inclusion composition and host crystal size has been discovered in a basaltic ash deposit from a volcanic arc setting. Least-evolved melt inclusions, featuring high H2O-CO2 saturation pressures, are found in large olivine crystals. Melt inclusion compositions become more evolved and volatile saturation pressures decrease as host crystal size decreases. This trend is interpreted as reflecting crystal nucleation and growth during decompression of a magma saturated with H2O and CO2. In general, melt inclusion compositions show large incompatible element enrichment and modest major element variation consistent with in situ crystallization. Crystal size is used to temporally constrain the formation age of melt inclusions and the decompression path of the magma. An estimated crystal growth rate of 10-8 cm s-1 yields an initial average magma ascent rate of ~4.8 km yr-1 at mid-crustal depths. At shallower depths the ascent rate was roughly an order of magnitude greater.
Keywords: VOLATILES; DEGASSING; MELTS; INCLUSIONS; IN SITU CRYSTALLIZATION